2016
DOI: 10.1073/pnas.1606779113
|View full text |Cite
|
Sign up to set email alerts
|

Tuning electronic transport via hepta-alanine peptides junction by tryptophan doping

Abstract: Charge migration for electron transfer via the polypeptide matrix of proteins is a key process in biological energy conversion and signaling systems. It is sensitive to the sequence of amino acids composing the protein and, therefore, offers a tool for chemical control of charge transport across biomaterial-based devices. We designed a series of linear oligoalanine peptides with a single tryptophan substitution that acts as a "dopant," introducing an energy level closer to the electrodes' Fermi level than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(124 citation statements)
references
References 68 publications
9
111
0
1
Order By: Relevance
“…Nevertheless, ETp comparisons showed that conduction via the helices was substantially higher than via the extended peptides. 155,410 In further work, coupling to the electrode contact was found to be critical for ETp efficiency across Au/7-peptide/Au junctions, as shown by comparing ETp between peptides with tryptophan (an amino acid with an aromatic indole side chain) in different positions along the chain. 403 In most biological ET processes, the cofactor of the protein is thought to enhance the electron tunneling probability with respect to vacuum tunneling.…”
Section: Electronic and Structural Properties Of Immobilized Proteinsmentioning
confidence: 99%
“…Nevertheless, ETp comparisons showed that conduction via the helices was substantially higher than via the extended peptides. 155,410 In further work, coupling to the electrode contact was found to be critical for ETp efficiency across Au/7-peptide/Au junctions, as shown by comparing ETp between peptides with tryptophan (an amino acid with an aromatic indole side chain) in different positions along the chain. 403 In most biological ET processes, the cofactor of the protein is thought to enhance the electron tunneling probability with respect to vacuum tunneling.…”
Section: Electronic and Structural Properties Of Immobilized Proteinsmentioning
confidence: 99%
“…Due to the ubiquity of hydrogen bonds in peptides, inter alia as a prime determinant of the three‐dimensional structure of proteins, this phenomenon is potentially of great importance. In the current article we examine it in detail, and explore its relevance to peptide function, for example, in electron transport and enzyme catalysis, post‐translational metabolism, and susceptibility and resistance to degradation in oxidative environments.…”
Section: Figurementioning
confidence: 99%
“…While this qualitative change is note ntirely unexpected, it is also of interestt oe xamine itsb iological impact. [7] Due to the ubiquity of hydrogen bonds in peptides, inter alia as ap rime determinant of the three-dimensional structure of proteins, [8] this phenomenon is potentially of great importance.I nt he current article we examinei ti nd etail,a nd explore its relevance to peptidef unction, fore xample, in electron transport [9, 10] and enzyme catalysis, [11, 12] post-translational metabolism, [13] and susceptibility and resistance [14] to degradation in oxidativee nvironments.Am ost characteristic feature of all peptides is the amide bond. We use as mall model system for this peptide backbone linkage,n amely, N-methylacetamide (Figure 1), to initially examine effects on IEs.…”
mentioning
confidence: 99%
“…31 This work is motivated by the experimental results of Ref. 34. In that paper, the authors reported that doping a 7-alanine (7A) homopeptide with a tryptophan unit can significantly enhance the conductance of junctions formed by contacting self-assembled monolayers (SAMs) to gold electrodes.…”
Section: Introductionmentioning
confidence: 98%